Processing of thymine glycol in a clustered DNA damage site: mutagenic or cytotoxic. - Bellon, S; Shikazono, N; Cunniffe, S; Lomax, M; O'Neill, P (Oxford University Press, 2009)
Localized clustering of damage is a hallmark of certain DNA-damaging agents, particularly ionizing radiation. The potential for genetic change arising from the effects of clustered damage sites containing combinations of AP sites, 8-oxo-7,8-dihydroguanine (8-oxoG) or 5,6-dihydrothymine is high. To date clusters containing a DNA base lesion that is a strong block to replicative polymerases, have not been explored. Since thymine glycol (Tg) is non-mutagenic but a strong block to replicative polymerases, we have investigated whether clusters containing Tg are highly mutagenic or lead to potentially cytotoxic lesions, when closely opposed to either 8-oxoG or an AP site. Using a bacterial plasmid-based assay and repair assays using cell extracts or purified proteins, we have shown that DNA double-strand breaks (DSBs) arise when Tg is opposite to an AP site, either through attempted base excision repair or at replication. In contrast, 8-oxoG opposite to Tg in a cluster 'protects' against DSB formation but does enhance the mutation frequency at the site of 8-oxoG relative to that at a single 8-oxoG, due to the decisive role of endonucleases in the initial stages of processing Tg/8-oxoG clusters, removing Tg to give an intermediate with an abasic site or single-strand break.